2018
DOI: 10.1186/s13075-018-1605-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of upper and lower limb exercise on the microvascular reactivity in limited cutaneous systemic sclerosis patients

Abstract: BackgroundAerobic exercise in general and high-intensity interval training (HIIT) specifically is known to improve vascular function in a range of clinical conditions. HIIT in particular has demonstrated improvements in clinical outcomes, in conditions that have a strong macroangiopathic component. Nevertheless, the effect of HIIT on microcirculation in systemic sclerosis (SSc) patients is yet to be investigated. Therefore, the purpose of the study was to compare the effects of two HIIT protocols (cycle and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 53 publications
3
50
1
1
Order By: Relevance
“…Our participants experienced how PA/exercises improved blood circulation and that they could have the potential to reduce the risk of digital ulcers and even the need of amputation. This is in line with a recent study that demonstrated the improved function of microvascular endothelial after exercises in SSc (Mitropoulos, Gumber, Crank, Akil, & Klonizakis, ). Whether exercise could have the potential to improve blood circulation in SSc‐individuals needs to be studied further in a randomized controlled trial, preferably including a patient‐reported outcome measure assessing perceived circulation as well as objective measurements.…”
Section: Essential For Life and Healthsupporting
confidence: 92%
“…Our participants experienced how PA/exercises improved blood circulation and that they could have the potential to reduce the risk of digital ulcers and even the need of amputation. This is in line with a recent study that demonstrated the improved function of microvascular endothelial after exercises in SSc (Mitropoulos, Gumber, Crank, Akil, & Klonizakis, ). Whether exercise could have the potential to improve blood circulation in SSc‐individuals needs to be studied further in a randomized controlled trial, preferably including a patient‐reported outcome measure assessing perceived circulation as well as objective measurements.…”
Section: Essential For Life and Healthsupporting
confidence: 92%
“…This is the first study to explore the microcirculatory effects of an exercise intervention, combining HIIT and RT, being used as an adjunct therapy to standard pharmacotherapy in people with lcSSc. The current study builds upon our previous work in this population (Mitropoulos et al, 2018a), aiming to provide important evidence, which would ultimately lead to a change in the therapeutic pathway for this clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise group undertook twice-weekly supervised exercise sessions at three different Sheffield sport venues: a) Centre of Sport and Exercise Science of Sheffield Hallam University, b) Graves sport centre and c) Concord sport centre. The HIIT protocol has been presented previously (Mitropoulos et al, 2018a). With respect to the RT, patients performed five upper body exercises in a circuit row for three circles interspersed by 2-3 minutes.…”
Section: Exercise Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Dass dies auch bei der Sklerodermie möglich ist, zeigen verschiedene, allerdings nicht randomisiert-kontrollierte Studien [35].EingeschränktgiltdieswohlauchfürPatientenmiteinerpul-monalenBeteiligung,LungenfibrosemitpulmonalerHypertonie, wobei mehr noch als bei Sklerodermie-Patienten ohne Lungenbeteiligung auf die reduzierte kardiopulmonale Belastbarkeit zu achtenist,diebeischwererAusprägungeineTrainingseignungauch ausschließenkann. AerobesTrainingistbeidersystemischenSkleroseabernoch auseinemanderenGrundinteressant.AusUntersuchungenmit PatientenmitperiphererAVKweißmanseitlangem,dasseinAusdauertraining auf dem Ergometer oder Laufband die periphere Mikrozirkulation in den Beinen verbessern und die schmerzfreie Gehstreckeverlängernkann [36].Einerandomisiert-kontrollierteStudie zeigte nun, dass auch bei Sklerodermie-Patienten ein gezieltes 12-wöchigesAusdauertraininginsbesonderemitHandergometern, wenigermitFahrradergometern,indenHändenzueinerverbesser-tenperipherenSauerstoffaufnahmeundvermindertenSchmerzen imRahmenderRaynaud-Symptomatikführte [37].Angabenzuobjektivierbaren Parametern der körperlichen Leistung wurden allerdingsnichtgeliefert.DieUntersuchungdeutetdaraufhin,dassein gezieltesAusdauertrainingderbetroffenenExtremitätenalternativ oder im Wechsel mit CO 2 -BädernzurnachhaltigenVerbesserung der Mikrozirkulation eingesetzt werden kann.…”
Section: Medizinische Trainingstherapieunclassified